The Contribution of Earth Bricks Reinforced with the Aqueous Maceration of Néré Pods (Parkia biglobosa) to Sustainable Construction in Togo: Characterization, Formulation, Mechanical Performance, and Recommendations - Magnouréwa Josiane Tossim; Cyprien Coffi Aholou; Yawovi Mawuénya Xolali Dany Ayité (Construction Materials, 2025)
Faced with environmental challenges posed by traditional building materials and the management of agricultural waste, this study uses dwarf hulls, an abundant waste product in West Africa, as a natural stabilizer for earth bricks. Three mixtures were studied: soil + water (reference), soil + néré husk decoction, and soil + decoction with weekly sprinkling. The results show a significant improvement in compressive strength with the decoction. At 28 days, it increases from 0.967 MPa (reference) to 1.251 MPa with decoction and 1.360 MPa with sprinkling. At 90 days, these values reach 1.060 MPa, 1.39 MPa, and 1.502 MPa, respectively, confirming the beneficial effect of tannins and humidification. On the other hand, the tensile strength decreased from 0.10 MPa for the reference mixture to 0.08 MPa and 0.08 MPa with decoction and sprinkling. This study highlights the potential of using néré husk as a durable stabilizer. However, further research is needed, particularly on the addition of plant fibers, to improve tensile strength.